TANTANGAN EKONOMI SYARIAH DALAM MENGHADAPI MASA DEPAN DI ERA GLOBALISASI - Siregar, Tetty Handayani; Nurhayati, Nurhayati; Anggraini, Tuti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
The purpose of this study is to analyze the factors that influence the development of Islamic Economics. These challenges include integration with the global market, development of competitive products and services, preparation of supportive regulations, and increasing public education and awareness. An integrated and collaborative strategy is needed to answer these challenges, involving the active role of the government, Islamic financial institutions, academics, and the community. This research method uses descriptive qualitative with data sources in the form of journals and books related to Islamic economics. The results of the study show that Islamic Economics faces increasingly diverse challenges along with the development of the global economy in the era of globalization. Dynamics such as changes in the structure of the global economy, the impact of technology, and innovation place Islamic Economics in a strategic position as well as full of challenges. This paper explores the main challenges faced by Islamic Economics in responding to future needs in the global era